Genetic population structure of harbour porpoises (Phocoena phocoena) in the North Sea and Norwegian waters - TOLLEY, KRYSTAL A.; ROSEL, PATRICIA E.; WALTON, MICHAEL; Bjorge, Arne; Oien, Nils (J. Cetacean Res. Manage., 1999)
The harbour porpoise (Plwcoena phocoena) is subject to a high rate of incidental mortality in fisheries worldwide and, in some areas, these rates are sufficiently high to warrant concern over population sustainability. Thus, the definition of sub-populations is paramount to the conservation of this species. To investigate the population structure in northeastern Atlantic waters, genetic sequence variation in mitochondrial DNA was examined in porpoises incidentally bycaught or stranded. The first 200 base-pairs of the control region were sequenced in 36 females and 47 males from Norwegian waters of the Barents and North Seas. In addition, 35 females and 31 males from United Kingdom waters, sequenced in a previous study (Walton, 1997) were included as a third study group. One haplotype was found to be common in all geographic groups, accounting for over 49% of all individuals sequenced. An analysis of molecular variance showed no significant difference among males from these regions. However, females showed a greater degree of genetic differentiation for both haplotype frequencies CFsT) and molecular diversity (¢iS1) than males. There was a significant difference (cx=0.05) in the haplotype frequencies between the Barents Sea and North Sea UK female porpoises when adjusted for multiple comparisons. Haplotype frequencies showed a significant difference between the North Sea UK and North Sea Norway females only after porpoises from the Shetland Islands were excluded from the North Sea UK sample. A phylogenetic tree revealed two main haplotypic clades, although there was little geographic structuring among these clades. These results are consistent with findings from other areas and suggest females are more philopatric than males. In spite of the lack of significant phylogenetic structuring, differing haplotype frequencies suggest that the North Sea UK and the Barents Sea sub-populations should be considered separate management units. In addition, haplotype frequency differences among the North Sea Norway and North Sea UK females (excluding Shetlands) also suggest the presence of separate management units within the North Sea.The harbour porpoise (Plwcoena phocoena) is subject to a high rate of incidental mortality in fisheries worldwide and, in some areas, these rates are sufficiently high to warrant concern over population sustainability. Thus, the definition of sub-populations is paramount to the conservation of this species. To investigate the population structure in northeastern Atlantic waters, genetic sequence variation in mitochondrial DNA was examined in porpoises incidentally bycaught or stranded. The first 200 base-pairs of the control region were sequenced in 36 females and 47 males from Norwegian waters of the Barents and North Seas. In addition, 35 females and 31 males from United Kingdom waters, sequenced in a previous study (Walton, 1997) were included as a third study group. One haplotype was found to be common in all geographic groups, accounting for over 49% of all individuals sequenced. An analysis of molecular variance showed no significant difference among males from these regions. However, females showed a greater degree of genetic differentiation for both haplotype frequencies CFsT) and molecular diversity (¢iS1) than males. There was a significant difference (cx=0.05) in the haplotype frequencies between the Barents Sea and North Sea UK female porpoises when adjusted for multiple comparisons. Haplotype frequencies showed a significant difference between the North Sea UK and North Sea Norway females only after porpoises from the Shetland Islands were excluded from the North Sea UK sample. A phylogenetic tree revealed two main haplotypic clades, although there was little geographic structuring among these clades. These results are consistent with findings from other areas and suggest females are more philopatric than males. In spite of the lack of significant phylogenetic structuring, differing haplotype frequencies suggest that the North Sea UK and the Barents Sea sub-populations should be considered separate management units. In addition, haplotype frequency differences among the North Sea Norway and North Sea UK females (excluding Shetlands) also suggest the presence of separate management units within the North Sea.